A Novel 4D Hyperchaotic System with Its Dynamical Analysis and Synchronization - Ozpolat, Erman; Gulten, Arif (Institute of Electrical and Electronics Engineers Inc., 2023)
The chaos can be explained as the order of nonlinear systems in disorder. When the structures exhibiting chaotic behavior are examined, they have an order within themselves as well as exhibiting complex and irregular behaviors. Chaotic time series feature a non-periodic structure that is susceptible to the initial conditions, such as bandwidth, noise, and similar. The chaotic system's behavior is significantly influenced by changes to the initial conditions. In chaotic systems, unlike randomness, there is an order within themselves. In comparison to chaotic systems, hyperchaotic systems have more sophisticated structures. This paper presents a novel four-dimensional hyperchaotic system and also carries out its synchronization. This synchronization process is designed for use in applications that require information hiding, such as secure communications. © 2023 IEEE.
11th International Symposium on Digital Forensics and Security, ISDFS 2023 -- 11 May 2023 through 12 May 2023 -- TN -- 189042
Keywords: Chaos; Hyperchaotic system; secure communication; synchronization